Analysis of Employment-Related Sentiment in Social Media in India - Meenakshi, Jaspreet Kaur (Mathematical Statistician and Engineering Applications, 2022)
The purpose of this article is to examine the unemployment rate in India and the employment sentiment index. The employment sentiment score, which is gathered from a lexicon-based technique and several social media channels, is utilized to categorize the feelings among three distinct groups depending on the keywords. In addition, the unemployment rate was acquired from the dataset in order to study the variations in the Indian rate of unemployment. From January 2020 to October2022, a total of 734,776 media messages were gathered, and their remarks were transformed into a sentiment score using machine learning algorithms. The employment score is compared to India’s unemployment rate. Despite the fact that the unemployment rate has become less variable in recent years, a negative sentiment score towards employment was discovered.